Letter from Carl D. Duncan to Patricia Whiting, October 12, 1964 - Duncan, Carl D. (Carl Dudley), 1895-1966:::Creator::::::::::::
Dr. Carl D. Duncan expresses his admiration for Patricia Whiting, particularly in relation to her interaction with international students.